The Importance of Minimally Invasive Therapy and Family Education Regarding Molluscum Contagiosum in Children - Sherlyna, Feby; Nugraha, Heru (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The Molluscum contagiosum virus (MCV), a member of the poxvirus family, is the cause of the widespread viral skin disease known as Molluscum contagiosum (MC). It primarily affects children aged 1–10 years, with an estimated global prevalence of 5–20%. A 2020 report from the Indonesian Ministry of Health documented MC as the third most common viral skin infection in children, with prevalence rates of 8–12% in densely populated regions like Jakarta and Surabaya. Usually confined to the face, torso, or extremities, the infection manifests as skin colored, dome-shaped papules with central umbilication. Transmission occurs via direct skin contact, autoinoculation, or contaminated things. While MC is self-limiting, treatment is often sought to prevent spread, alleviate cosmetic concerns, or address persistent lesions. This case highlights a typical presentation of MC in a toddler and underscores the importance of family education and minimally invasive therapies. The treatment we gave to this patient was in the form of cantharidine 0.7% (left for 4 hours then rinsed) and mupirocin cream 2% (used if the bumps/papules have broken). The patient’s family was also educated about preventing disease transmission, such as not touching, scratching, or squeezing papules, diligently cleaning hands by washing hands in running water or using wet wipes that are safe for babies, and avoiding sharing personal items.